Cross-linguistic Generalizations in the Verb-Production Treatment of Bilingual Aphasic Speakers - Obeidat, Hussein A.; Abu Jamous, Heba (Dirasat: Human and Social Sciences, 2023)
Objectives: This study investigates cross- linguistic generalizations in the verb-production therapy for one bilingual speaker with non-fluent aphasia. Methods: Intensive sixty-hour treatment sessions over a period of 12 weeks was provided for an unbalanced bilingual speaker with mild to severe aphasia. A combination of semantically and phonologically cued verbs as well as communication-based treatment were administrated. The treatment was provided in the patient’s L1. The Bilingual Aphasia Test and action-naming pictures from The Newcastle University Aphasia Therapy Resources were used for the pre-and-post-therapy assessments for both languages. Results: A cross-language generalization was reported from L1 to L2. A significant generalization was found in one linguistic domain, i.e., semantics. A within-language generalization was found, i.e., the untrained verbs of L1 showed significant improvement. Nonetheless, inhibition of the semantic domain of the patient’s L1 was reported. Providing treatment for the stronger language of a bilingual aphasic individual could lead to cross-language transfer to the untreated weaker language. Conclusions: We suggest that the cross-language generalization is reported due to the structural overlap between the two languages.